Strategi Pemasaran Bakpia Porang (Amorphophallus Muelleri) di UD.Cakrawala Kelurahan Hewuli Kecamatan Alok Barat Kabupaten Sikka - Alice Seliku; Yoseph Yakob Da Rato (Peneliti.net, 2022)
Marketing strategy is an effort to market a product, be it goods or services, using certain patterns of plans and tactics so that the number of sales becomes higher. The purpose of this research is to find out the marketing strategies of people in UD. Horizon through SWOT analysis. The results of the study using SWOT analysis in UD. Cakrawala, that the application of strategies to the company using Growth Oriented Strategy. This is because, in the cartesius diagram of SWOT analysis shown that the highest total score value is in the first quadrant where the quadrant is a very favorable situation. UD. Horizon has many opportunities and strengths so that it can seize and take advantage of existing opportunities while minimizing weaknesses and overcoming various threats